Investigation of the role of Lip5 - a member of the secreted lipase gene family - in the virulence of Candida albicans - Hamari, Zsuzsanna (Acta Biologica Szegediensis, 2013)
Candida albicans (Ca) is the most common species isolated from invasive candidiasis. It has been shown that secreted lipases of Ca contribute to the virulence of the fungus during infection. In this study, we generated heterozygous and homozygous lipase 5 (LIP5) mutants in Ca by the caSAT1-flipper technique. Notably, the Southern-hybridization results indicated a yet unknown allelic heterozygosity in LIP5 in our laboratory strain. Quantitative reverse transcription-PCR experiments demonstrated the absence of LIP5 expression in the homozygous knockout mutants. However, the knock out mutants showed no alteration in the rate of fungal growth, cell and colony morphology under temperature, pH or osmotic stress in comparison to wild type cells. In vitro infection studies using the J774.2 murine macrophage-like cell line revealed no alteration in the virulence of mutant cells. Thus, we conclude that the deletion of LIP5, somewhat surprisingly, has no effect on the physiology or virulence of Ca in our experimental setting.